Shooting for an economic "miracle": German post-war neoliberal thought in China's market reform debate - Isabella Weber (University of Massachusetts, Department of Economics, 2021)
This paper develops a comparative and connected history of the debates over transition to a market economy in West-Germany after World War II and in China during the first decade of reform and opening up under Deng Xiaoping (1978-1988). At both historical moments the political aim was to reintroduce market mechanisms into a dysfunctional command economy. The question what kind of price reform this required was subject to heated debates among economists. This paper shows how the West-German 1948 currency and price reform was introduced into the Chinese reform debate by German ordoliberals and neoliberals like Friedman. It traces how the West-German case study was mystified as "Erhard Miracle" and became a metaphor for the vision of universal overnight price liberalisation in China - a core element of shock therapy.
Keywords: 330; Neoliberalism; Socialism; China; Germany; Market transition; Price theory